Platelet-activating factor receptor (PAFR) regulates neuronal maturation and synaptic transmission during postnatal retinal development - Dalmaso, Barbara; Liber, Andre Mauricio Passos; Ventura, Dora Fix; Jancar, Sonia; Del Debbio, Carolina Beltrame (Frontiers in Cellular Neuroscience, 2024)
Platelet-Activating Factor (PAF), PAF receptor (PAFR), and PAF-synthesis/degradation systems are involved in essential CNS processes, such as neuroblast proliferation, differentiation, migration, and synaptic modulation. The retina is an important Central Nervous System (CNS) tissue for visual information processing. During retinal development, the balance between Retinal Progenitor Cell (RPC) proliferation and differentiation is crucial for proper cell determination and retinogenesis.Despite its importance in retinal development, the effects of PAFR deletion on RPC dynamics are still unknown. Here, we show that PAFR knockout mice (PAFR -/-) increased the proliferation during postnatal retinogenesis and altered the expression of specific differentiation markers. As a result, the retinas of postnatal PAFR -/-animals decreased neuronal differentiation and synaptic transmission markers, leading to differential responses to light stimuli measured with electroretinography (ERG).Our findings suggest that PAFR signaling plays a critical role in regulating the postnatal RPC cell differentiation dynamics, participating in retinal development, cell organization, and neuronal circuitry formation.